A therapeutic oxygen carrier isolated from Arenicola marina decreases amanitin-induced hepatotoxicity. (September 2021) - Le Daré, Brendan; Ferron, Pierre-Jean; Bellamri, Nessrine; Ribault, Catherine; Delpy, Eric; Zal, Franck; Lagente, Vincent; Gicquel, Thomas
Abstract: The amanitins (namely α- and β-amanitin) contained in certain mushrooms are bicyclic octapeptides that, when ingested, are responsible for potentially lethal hepatotoxicity. M101 is an extracellular hemoglobin extracted from the marine worm Arenicola marina . It has intrinsic Cu/Zn-SOD-like activity and is currently used as an oxygen carrier in organ preservation solutions. Our present results suggest that M101 might be effective in reducing amanitin-induced hepatotoxicity and may have potential for therapeutic development. Graphical abstract: Image 1 Highlights: α- and β-amanitin lead to cell death and mitochondrial reactive oxygen species production in differentiated HepaRG cells. M101 is effective in reducing amanitin-induced cell death and mitochondrial reactive oxygen species production in vitro. M101 might be effective in reducing amanitin-induced hepatotoxicity and may have potential for therapeutic development.